Peningkatan Hasil Belajar bolavoli melalui modifikasi alat pada siswa putri MA - Armansyah Arman (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
This research analyzes the data by reducing the data and presenting the data in tabular form, looking for the average value and percentage of learning completeness. The sample in this study was 31 daughters of MA Amir AL-Jannah. The results of cycle I showed that the results of learning volleyball in terms of cognitive aspects were (26%) 8 students who completed, and (74%) 23 students who did not complete. From the affective aspect there were (55%) 17 students who completed and (45%) There were 14 students who had not completed the psychomotor aspect as much as (45%) 14 students had completed it and (55%) 17 students had not completed it, 12 students had completed it and 19 students had not completed it. In cycle II, it showed that the results of learning volleyball through tool modification were in terms of the affective aspect as many as (94%) 29 students completed and (6%) two students did not complete, from the cognitive aspect as many as (94%) 29 students completed and (6%) two students did not complete, from the psychomotor aspect as many as (90%) 28 students completed and (10%) three students did not complete. Based on the results of the data analysis above, it can be said that using modified volleyball equipment can improve volleyball learning outcomes for female students at MA Amir AL-Jannah in terms of attitudes, abilities and knowledge.